Strategi Pemasaran Pada Hainun Store - Syahrani, Safrelia Salsabiella; Sukaris (Cattleya Darmaya Fortuna, 2024)
The purpose of this research is to find out the marketing strategies implemented by Hainun Store and to find out segmentation, targeting and positioning at Hainun Store. The method used in this research is qualitative with a field research approach. The data collection techniques used are interviews and documentation. Data analysis in this study used the Miles and Huberman data analysis model. The results showed that market segmentation was carried out by dividing consumers into groups based on age, gender, income, and occupation, with a focus on women, especially students and office workers, as well as middle-class people. The targeting applied is a concentrated renovation strategy, which focuses marketing efforts on these specific customer groups, to meet their fashion needs. Hainun Store's positioning is done by emphasising good product quality, affordable prices, and a comfortable store atmosphere, to differentiate themselves from competitors and ensure that their products are remembered as the first choice in the minds of consumers.